INVESTIGATION ON THE ENVIROMENTAL EFFECT OF LOCAL PRODUCTION METHOD OF ALUMINIUM UTENSIL IN KANO - Yakubu, Y. I.; Yola, I. A. (FUDMA JOURNAL OF SCIENCES, 2020)
This research investigated the environmental effect of local production methods of aluminium utensils in Bachirawa, Ungogo local government Kano. Three soil samples and two samples of water were collected from sites A, B,C, D and E. The samples were then taken to faculty of agriculture for analysis. Atomic absorption spectrophotometer (A A S model No 240 FSAA) was used to determine the concentration levels of heavy metals in the samples. The results show that, the concentration levels of  heavy metals in the soil samples A, B and C are:  Zn ranges between  (1158.13 - 11,117.80)  mg/kg; Mn  between  (285.719 â€“ 1809.672) mg/kg; Cd between (0.026 â€“ 0.540) mg/kg; Cr (0.498 â€“ 0.832) mg/kg and Pb between (42.54 - 285.53) mg/kg. The observed concentration levels in water samples for Zn ranges between (0.2411 â€“ 0.4435)mg/l; Cd between (0.091 â€“ 0.123) mg/l; Cr between (0.015 â€“ 0.022) mg/l; Mn between (0.284 â€“ 0.728) mg/l and Pb between (0.00-0.08) mg/l. Zinc and Manganese have higher concentration levels than the recommended  permissible limit set by European Union (EU) and  United Kingdom(UK)  while Cd, Cr and  Pb have lower concentration levels than the recommended permissible limit set by EU and UK in soil samples  A, B and C. The concentration levels of Mn, Cd and Pb in water samples were higher than the permissible limit set by World Healh Organization (WHO) whereas Zn and Cr have concentrations lower than the recommended permissible limit set by
Keywords: Pollution; Utensils, Absorption, Concentration, Spectrophotometer, Permissible